(untitled) (American Journal of Technology and Applied Sciences, 2024)
Recurrent bronchitis occupies one of the leading places among respiratory diseases in children and requires a careful approach from pediatricians, since it is a risk factor for the subsequent development of a number of chronic respiratory diseases. The occurrence of recurrent bronchitis is associated with an acute respiratory viral infection and occurs under the influence of unfavorable environmental factors: passive smoking, air pollution, poor living conditions; presence of a burdened perinatal history. Episodes of recurrent bronchitis in children are characterized by inflammatory changes in the bronchial mucosa, weakening of local protective factors, mild obstructive disorders, as well as cytomorphological changes in the cellular composition of induced sputum and degeneration of the ciliated epithelium). The use of combination drugs as a means of initial therapy has a positive effect on the clinical course of recurrent bronchitis in children and accelerates recovery, which is due to its normalizing effect on mucociliary clearance, nonspecific factors of local immune defense of the bronchial mucosa, as well as mucokinetic and indirect anti-inflammatory effects.